THE TOXIC PROPERTIES OF SERUM EXTRACTS OF HEMOLYTIC STREPTOCOCCI - Weld, Julia T. (The Rockefeller University Press, 1934)
1. A method is described whereby toxic substances may be extracted from hemolytic streptococci with inactivated serum. 2. Such extracts contain large amounts of hemotoxin and leucocidin. 3. Their intravenous injection into mice causes marked hemoglobinuria, anemia, and death. 4. There is evidence that this anemia is not the only cause of death of these animals. 5. Incomplete work seems to indicate that the hemotoxin and the lethal poisons are not antigenic. 6. Certain biological properties of the extract are described.